Konsepsi Geometri pada Etnomatematika Pane Sebagai Sumber Belajar Matematika di Sekolah Dasar - Inzoni; Neza Agusdianita (Universitas Bengkulu, 2022)
This study aims to identify and describe the geometrical concepts of flat shapes and geometric shapes on the Ethnomathematics pane as a source of learning Mathematics at the Kepahiang District Elementary School. This research is a qualitative research with a grounded theory approach. The population in this study is the Rejang tribe in Kepahiang Regency and the sample in this study is the traditional pane tool craftsman of the Rejang tribe in Daspetah village, Kepahiang district. The main research instrument used in the form of the researcher himself and supporters in the form of observation, interviews, and documentation. The technique used in analyzing the research data uses standard data from grounded theory. The geometric conception in the traditional pane tool of the Rejang tribe has the concept of a flat shape in the form of circles and rectangles and there is also the concept of an open tube space. In addition, other findings were also found in the form of arithmetic lines and the results of material validation obtained were 82,3% with a very valid category, so that the mathematical concepts contained in the Rejang tribal pane traditional tool can be used as a learning resource in the form of offering Mathematics learning media in Elementary Schools.